2021
DOI: 10.51201/jusst/21/09648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Level of Claudin‐ 3 and Its Association with Disease Severity in Patients with Psoriasis in Iraqi patients

Abstract: Background Psoriasis is a prevalent inflammatory skin disease. Psoriasis is a complex illness in which environmental variables acting on individuals with unique genetic predisposition causing immunological dysregulation. Claudins are transmembrane proteins that help to generate tight junctions by binding to the actin cytoskeleton. Claudin 3 in the blood is thought to be a good indicator of intestinal permeability. Objective: The aim of this study was to detect of the alteration of claudin-3 in psoriasis patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In the present study, serum CLD-3 level was significantly higher than the control group before treatment (0 th hours) (Table 3, Figure 1D). We believe that the potential cause of the rise before therapy may be connected to the rise in CLD-3 release as a preventative measure to reinforce the intestinal tight junctions during the early stage of intestinal injury, as reported by other researchers (Sikora et al, 2019;Ahmed et al, 2021). In addition, there are positive correlations between CLD-3 and I-FABP (p<0.01), IL-8 (p<0.05), ACTG2 (p<0.01), and IAP (p<0.05) levels (Table 4) showing that these biomarkers have essential relationships between the body's inflammatory response, damage, and repair to the pathological condition in the intestines due to different causes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In the present study, serum CLD-3 level was significantly higher than the control group before treatment (0 th hours) (Table 3, Figure 1D). We believe that the potential cause of the rise before therapy may be connected to the rise in CLD-3 release as a preventative measure to reinforce the intestinal tight junctions during the early stage of intestinal injury, as reported by other researchers (Sikora et al, 2019;Ahmed et al, 2021). In addition, there are positive correlations between CLD-3 and I-FABP (p<0.01), IL-8 (p<0.05), ACTG2 (p<0.01), and IAP (p<0.05) levels (Table 4) showing that these biomarkers have essential relationships between the body's inflammatory response, damage, and repair to the pathological condition in the intestines due to different causes.…”
Section: Discussionsupporting
confidence: 52%
“…Zeissig et al (2007) reported that CLD-3 concentration was lower in people with Crohn's disease, indicating intestinal barrier dysfunction. However, it has been reported that CLD-3 level is higher in Psoriasis patients than in healthy people (Sikora et al, 2019;Ahmed et al, 2021), CLD-2 and CLD-3 levels are significantly increased in Celiac patients (Adriaanse et al, 2017). It has been reported that CLD -3 concentrations are lower in premature calves with respiratory distress syndrome (Yıldız et al, 2019) and calves with neonatal diarrhoea (Ok et al, 2020) than in healthy calves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation